Comparing Non-invasive Inverse Electrocardiography With Invasive Endocardial and Epicardial Electroanatomical Mapping During Sinus Rhythm - Roudijk, Robert W.; Boonstra, Machteld J.; Brummel, Rolf; Kassenberg, Wil; Blom, Lennart J.; Oostendorp, Thom F.; te Riele, Anneline S. J. M.; van der Heijden, Jeroen F.; Asselbergs, Folkert W.; van Dam, Peter M.; Loh, Peter (Frontiers in Physiology, 2021)
This study presents a novel non-invasive Equivalent Dipole Layer (EDL) based inverse electrocardiography (iECG) technique which estimates both endocardial and epicardial ventricular activation sequences. With iECG, functional substrate imaging in patients with cardiomyopathy and sudden cardiac death risk stratification may be aided. We aimed to quantitatively compare this novel iECG approach with invasive electro-anatomical mapping (EAM) during sinus rhythm. Thirteen patients (77% males, 48±20 years old) referred for endocardial and epicardial EAM underwent 67-electrode body surface potential mapping and CT imaging. The EDL-based iECG approach was improved by mimicking the effects of the His-Purkinje system on ventricular activation. EAM local activation timing (LAT) maps were compared with iECG LAT-maps using absolute differences (AD) and Pearson’s correlation coefficient (CC), reported as mean±standard deviation [95% confidence interval]. The CC between iECG LAT-maps and EAM was 0.54±0.19 [0.49-0.59] for epicardial activation, 0.50±0.27 [0.41-0.58] for right ventricular (RV) endocardial activation and 0.44±0.29[0.32-0.56] for left ventricular (LV) endocardial activation. The AD in timing between iECG maps and EAM was 17.4±7.2ms for epicardial maps, 19.5±7.7ms for RV endocardial maps, 27.9±8.7ms for LV endocardial maps. The absolute distance between RV endocardial primary breakthrough sites was 30±16mm and 31±17mm for the LV. The absolute distance for latest epicardial activation was median 12.8 [IQR: 2.9–29.3] mm. This first in-human quantitative comparison of iECG estimations and invasive LAT-maps on both the endocardial and epicardial surface during sinus rhythm showed improved agreement, although with considerable AD and moderate CC. Non-invasive iECG requires further refinements to facilitate clinical implementation and risk stratification.